Studies of gel polymer electrolytes for lithium and sodium batteries / Khairul Bahiyah Isa - Khairul Bahiyah, Isa (2016)
In the present work, gel polymer electrolytes (GPEs) comprising polyvinylidene-co-hexafluoropropylene (PVdF-HFP) as host polymer in a mixture of ethylene carbonate (EC) and propylene carbonate (PC) plasticizing solvent with various concentrations of lithium triflate and sodium triflate dopant salts have been prepared by the solution casting technique. Three systems of polymer electrolytes films have been prepared; these systems are the plasticized-PVdF-HFP system i.e. PVdF-HFP/EC/PC system and two plasticized-salted PVdF-HFP systems i.e. PVdF-HFP/EC/PC/LiCF3SO3 and PVdF-HFP/EC/PC/NaCF3SO3. The pure PVdF-HFP film serves as reference. Using results from impedance spectroscopy, ionic conductivity for each film in all systems has been calculated. The room temperature conductivity for pure PVdF-HFP film and plasticized-PVdF-HFP film is 1.86 x 10-11 S cm-1 and 3.31 x 10-8 S cm-1, respectively. The room temperature-conductivity for the highest conducting film in PVdF-HFP/EC/PC/LiCF3SO3 system and PVdF-HFP/EC/PC/NaCF3SO3 system are 1.40 x 10-3 S cm-1 and 2.50 x 10-3 S cm-1 respectively. The conductivity of the PVdF-HFP-based polymer electrolyte has been found to be salt concentration dependent which is attributed to the increase in the number of mobile ions within the polymer matrix. The binary plasticizing solvent helps to increase the amorphous content of the polymer matrix and tend to dissociate ion-pairs into free cations and anions thereby leading to an overall enhancement in conductivity. The conductivity-temperature studies are then performed on the highest conducting film from the in PVdF-HFP/EC/PC/LiCF3SO3 system and PVdF-HFP/EC/PC/NaCF3SO3 system. The plots of conductivity versus inverse temperature for both systems follow the VTF rule. The activation energy for all the GPE films are determined to be in the range of 0.08 - 0.102 eV. The transport number of lithium and sodium ions in the GPEs was evaluated using the combination of AC impedance spectroscopy and DC polarization techniques. DSC studies show that the Tg of the GPE film decreases upon addition of the plasticizing solvents and the salts. This result is in good agreement with the conductivity behaviour. TGA analysis shows that the samples with higher salt concentrations have greater thermal stability. FTIR and Raman studies confirm that conductivity enhancement is due to increase in free ions and decrease in ion aggregates. XRD studies show the occurrence of complexation between the polymer, the plasticizing solvents and the salts. The FESEM micrographs show that the presence of the plasticizing solvents in PVdF-HFP/salt system helped to obtain regular pore structure, which can increase ion mobility and conductivity. The electrochemical stability of the GPE films has been tested using linear sweep voltammetry (LSV) and the value of working voltage range appears to be high enough to be used as an electrolyte in lithium and sodium cells. Studies based on AC impedance and cyclic voltammetry (CV) confirmed the lithium and sodium ion conduction in the GPE films from both systems. The LiNiCoO2 | GPE| Li and MnO2| GPE| Na cells have been assembled and their performances have been evaluated. The cells that containing LiCF3SO3 and NaCF3SO3 salt exhibits the first capacity of 164 mAhg-1 and 168 mAhg-1, respectively.